(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Adapting sensor nodes to suit their specific sensing and communication capabilities can pose challenges, especially in harsh environments. Therefore, finding an optimal solution heavily depends on the deployment context. In this study, we aim to eliminate blind spots by considering the trade-offs between power consumption and sensor coverage among consecutive nodes. We calculate and monitor the relationship between the available power and the area that sensors can effectively cover over a defined time frame. Additionally, we investigate a pair of sensors with specific characteristics related to their remaining energy and sensing range. To analyze the data, logistic regression is employed, taking into account the aspects of residual energy and the communication capabilities of these sensors.